Are listed banks riskier than private banks? - Mehran, Hamid; Patel, Ajay; Sorokina, Nonna (Journal of Financial Stability, 2025)
We shed light on the narrative that listing contributes to risk-taking by examining the risk characteristics of listed BHCs, small enough to be private, against a sample of comparable private BHCs, large enough to be listed, over the 1987–2019 period. We measure our proxies for risk characteristics over different intervals in the sample period to account for the effect of new regulations and variation in the intensity of information production by regulators, markets, and financial firms. We document that listed banks are riskier than private banks over the 22-year sample period. Examining the subperiods, we find that listed banks are riskier than private banks before the crisis, but they may not be as risky following the crisis. While risk increases for all banks during the crisis, the increase in risk for listed banks during the crisis is greater than that for private banks. Our findings are both statistically and economically significant and suggest that financial reforms and regulatory expectations facing banks post-crisis might have contributed to the risk reduction for listed banks relative to private banks.